Apparent reduction in the size of one side of the face associated with a small retrosplenial haemorrhage. Issue 1 (January 1991) - Ebata, S; Ogawa, M; Tanaka, Y; Mizuno, Y; Yoshida, M
Abstract : A 68 year old Japanese female with unilateral metamorphopsia of the face that developed after a small haemorrhage in the contralateral retrosplenial region, is described. The patient claimed that the right side of a face, that is, the left side when looked at by the patient, appeared smaller than the left. In addition, her drawings of the face showed some distortions. Objects other than the face were perceived normally. Cranial CT scan revealed a small high density area in the right retrosplenial region. The face appears to have a special representation in the posterior hemisphere.